2020
DOI: 10.1073/pnas.2000715117
|View full text |Cite
|
Sign up to set email alerts
|

Sustained representation of perspectival shape

Abstract: Arguably the most foundational principle in perception research is that our experience of the world goes beyond the retinal image; we perceive the distal environment itself, not the proximal stimulation it causes. Shape may be the paradigm case of such “unconscious inference”: When a coin is rotated in depth, we infer the circular object it truly is, discarding the perspectival ellipse projected on our eyes. But is this really the fate of such perspectival shapes? Or does a tilted coin retain an ellipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 71 publications
4
69
2
Order By: Relevance
“…Each shelf contained four head-on elliptical coins and four circular coins (two head on, two rotated) (Figure 1.1A). Importantly, unlike Experiments 8 and 9 reported in Morales et al (2020), where the shelves were 250cm away from the far end of the table where subjects viewed the stimuli, in the present experiment (Experiment S1), the shelves were placed at an 80cm viewing distance. All the coins were carefully angled to look either head on or rotated 45º from the subject's chair at this specific viewing distance.…”
Section: Stimulimentioning
confidence: 92%
See 4 more Smart Citations
“…Each shelf contained four head-on elliptical coins and four circular coins (two head on, two rotated) (Figure 1.1A). Importantly, unlike Experiments 8 and 9 reported in Morales et al (2020), where the shelves were 250cm away from the far end of the table where subjects viewed the stimuli, in the present experiment (Experiment S1), the shelves were placed at an 80cm viewing distance. All the coins were carefully angled to look either head on or rotated 45º from the subject's chair at this specific viewing distance.…”
Section: Stimulimentioning
confidence: 92%
“…The setup and procedure for this experiment was almost identical to Experiment 9 in Morales et al (2020), where full details about the methods can be found. Here we summarize the most important elements of the task design and highlight the specific differences of this experiment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations